Interpenetrated Structures for Enhancing Ion Diffusion Kinetics in Electrochemical Energy Storage Devices - Xue, Xinzhe; Feng, Longsheng; Ren, Qiu; Tran, Cassidy; Eisenberg, Samuel; Pinongcos, Anica; Valdovinos, Logan; Hsieh, Cathleen; Heo, Tae Wook; Worsley, Marcus A.; Zhu, Cheng; Li, Yat (Nano-Micro Letters, 2024)
The architectural design of electrodes offers new opportunities for next-generation electrochemical energy storage devices (EESDs) by increasing surface area, thickness, and active materials mass loading while maintaining good ion diffusion through optimized electrode tortuosity. However, conventional thick electrodes increase ion diffusion length and cause larger ion concentration gradients, limiting reaction kinetics. We demonstrate a strategy for building interpenetrated structures that shortens ion diffusion length and reduces ion concentration inhomogeneity. This free-standing device structure also avoids short-circuiting without needing a separator. The feature size and number of interpenetrated units can be adjusted during printing to balance surface area and ion diffusion. Starting with a 3D-printed interpenetrated polymer substrate, we metallize it to make it conductive. This substrate has two individually addressable electrodes, allowing selective electrodeposition of energy storage materials. Using a Zn//MnO2 battery as a model system, the interpenetrated device outperforms conventional separate electrode configurations, improving volumetric energy density by 221% and exhibiting a higher capacity retention rate of 49% compared to 35% at temperatures from 20 to 0 °C. Our study introduces a new EESD architecture applicable to Li-ion, Na-ion batteries, supercapacitors, etc. Highlights: 1 A new and compact device configuration was created with two interpenetrated, individually addressable electrodes, allowing precise control over the geometric features and interactions between the electrodes. 2 The interpenetrated electrode design improves ion diffusion kinetics in electrochemical energy storage devices by shortening the ion diffusion length and reducing ion concentration inhomogeneity. 3 The device with interpenetrated electrodes outperformed the traditional separate electrode configuration, enhancing both volumetric energy density and capacity retention rate.